2017
DOI: 10.2169/internalmedicine.56.7930
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Proliferative Glomerulonephritis in a Patient Diagnosed to Have Hypoparathyroidism, Sensorineural Deafness, and Renal Dysplasia (HDR) Syndrome with a Novel Mutation in the <i>GATA3</i> Gene

Abstract: Hypoparathyroidism, sensorineural deafness, and renal dysplasia (HDR) syndrome is a rare autosomal dominant disease caused by GATA3 mutations. Although several cases with variable renal features have been reported, the presence of histological changes within the glomeruli in adult patients is unclear. We herein report an adult case of HDR syndrome with a novel p.C288W (TGC>TGG) missense mutation in GATA3. His renal histology showed a membranoproliferative glomerulonephritis-like glomerular lesion. Additional r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…11213 HDR often results in progressive kidney disease caused by congenital renal aplasia, hypoplasia, or dysplasia (41%); vesicoureteral reflux (16%); and cysts or pelvicalyceal deformities (11%). 14 More recently, HDR has been associated with nephrotic syndrome and isolated cases of GN, 15,16 whereas Gata3 hypomorphic mutant mice rescued with a yeast artificial chromosome Gata3 transgene, whose expression was limited to renal tubules and not glomeruli, have been shown to suffer glomerular mesangial cell (MC) defects. 17 In genome-wide transcriptome studies, GATA3 has been identified as a highly enriched transcript in MCs, 18,19 but the functional significance of GATA3 expression in MCs in health and disease has not been explored.…”
Section: Resultsmentioning
confidence: 99%
“…11213 HDR often results in progressive kidney disease caused by congenital renal aplasia, hypoplasia, or dysplasia (41%); vesicoureteral reflux (16%); and cysts or pelvicalyceal deformities (11%). 14 More recently, HDR has been associated with nephrotic syndrome and isolated cases of GN, 15,16 whereas Gata3 hypomorphic mutant mice rescued with a yeast artificial chromosome Gata3 transgene, whose expression was limited to renal tubules and not glomeruli, have been shown to suffer glomerular mesangial cell (MC) defects. 17 In genome-wide transcriptome studies, GATA3 has been identified as a highly enriched transcript in MCs, 18,19 but the functional significance of GATA3 expression in MCs in health and disease has not been explored.…”
Section: Resultsmentioning
confidence: 99%
“…In an extensive review of the literature, we found 173 reported patients. In this report, we review these patients and an additional seven patients observed by the authors (A. Y. Barakat, personal communication, 2017) for a total of 180 patients (Adachi, Tachibana, Asakura, & Tsuchiya, ; Aksoylar et al, ; Ali et al, ; Al‐Shibli, Al Attrach, & Willems, ; Bahceci, Salgur, Tutuncuoglu, Yilmaz, & Oruk, ; Barakat, D'Albora, Martin, & Jose, ; Beetz et al, ; Belge et al, ; Bernandini et al, ; Bilous et al, ; Boysan et al, ; Chen et al, ; Chenouard et al, ; Cheon, Kim, & Yoo, ; Chiu, Chen, Chao, Yann, & Tsai, ; Chu et al, ; Civan et al, ; Doneray, Usui, Kaya, & Dönmez, ; Ferdoush, Mutanabbi, Talukder, Al Helal, & Kawser, ; FernĂĄndez et al, ; Ferraris et al, ; Fujimoto et al, ; Fukami et al, ; Gaynor et al, ; Gomes et al, ; Goodwin, Hawley, & Miller, ; Hameed et al, ; Hasegawa et al, ; HernĂĄndez et al, ; Higuchi et al, ; Kamezaki et al, ; Kato, Wada, Numata, & Kakizaki, ; Kim et al, ; Kostoglou‐Athanassiou, Stephanopoulos, Karfi, & Athanassiou, ; Lichtner et al, ; Maleki, Bashardoust, Alamdri, & Tavosi, ; Maloo ; Meena, Maloo, Samar, Ruhela, & Saini, ; Melis et al, ; Mino et al, ; Moldovan, Carvalho, Jorge, & Medeira, ; Muroya et al, ; Muroya et al, ; Mutlu, Kırmızıbekmez, Nakamura, Fukami, & Hatun, ; Nakamura et al, ; Nanba et al, ; Nesbit et al, ; Ni & Htet, ; Ohta et al, ; Pollak‐Hainz, Bartsch, Zechner, & Keilmann, ; Ranjbar‐Omrani, Zamiri, Sabayan, & Mohammadzadeh, ; Rodriguez Benitez et al, ; Sau, Chat...…”
Section: History Of the Syndromementioning
confidence: 99%
“…Nephrotic syndrome, hematuria, proteinuria, proximal and distal renal tubular acidosis, nephrocalcinosis, and CKD have also been described (Barakat et al, ; Bilous et al, ; Hameed et al, ; Kato et al, ; Muroya et al, ; Ni & Htet, ; Taslipinar et al, ; Van Esch et al, ). Although GATA3 is strongly expressed in the collecting ducts and weekly in glomerular mesangial cells (Labastie, Catala, Gregoire, & Peault, ), Kamezaki et al () reported one case of glomerulonephritis in a patient with this syndrome. This could have been a coincidental finding.…”
Section: Clinical Characteristicsmentioning
confidence: 99%
“…A total of 4 cases were reported from our country. In addition to classical findings in patients with HDR syndrome, Hirschsprung disease [9], renal tubular acidosis, autoimmune thyroiditis, hypergonadotropic hypogonadism [10], biliary atresia [11], ichthyosis [12], severe mental retardation [13], congenital choanal atresia [14], psoriasis [15], squamous cell lung carcinoma [16], band keratopathy, pigmentary retinopathy [17], nephrocalcinosis [18], cerebral infarction [19], recurrent cerebral infarction [20], tumoral calcinosis [21], and proliferative glomerulonephritis [22] were reported in previous publications.…”
Section: Discussionmentioning
confidence: 99%